The effects of quercetin on oxidative stress and fibrosis markers in chronic kidney disease rat model (Medical Journal of Indonesia, 2017)
Background: Oxidative stress may play a role in the pathogenesis of (CKD), Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor involved in cell defense mechanism against oxidative stress. In this study, we examined the effect of quercetin, a polyphenplic antioxidant anti fibrosis compund in fruits and vegetables, on the 5/6 nephrectomy-induced CKD progression model rats through modulation of Nrf2 expression.Methods: Male Sprague-Dawley rats were randomly divided into normal control group (C), untreated 5/6 nephrectomy (Nx), quercetin-treated 5/6 nephrectomy (100 mg/kgBW/day orally) (NxQ), and captopril-treated 5/6 nephrectomy (10 mg/kgBW/day orally) (NxK) for 8 weeks. At the end of study, all animals were sacrified. Urine, blood, and kidney tissues were taken for examination of proteinuria, plasma creatinine, urea, malondialdehyde (MDA), glutathione peroxidase (GPx) activity, Nrf2, Keap1, heme oxygenase-1 (HO-1) expressions, and renal fibrosis.Results: Quercetin administration did not affect the level of protein in urine, plasma creatinine, and urea. However, it tended to reduce the level of MDA, increase GPx activity, Nrf2, Keap1, and HO-1 expression as well as the degree of fibrosis.Conclusion: In 5/6 nephrectomized rats, quercetin tended to ameliorate the level of MDA, GPx activity, Nrf2, Keap1, and HO-1 expression. In addition, quercetin tended to decrease the degree of fibrosis in the remnant kidney.